1
$\begingroup$

I am working this question:

Set $B = \{(x, y)\mid 1 \le x^2 + y^2 \le 4\}$, $A_\alpha = \{(x, y)\mid x^2 + y^2 = α^2\}$. Prove that $\bigcup\{A_\alpha\mid \alpha \in [1, 2]\} = B$.

because this is a equality, I need to prove it into two cases.

Proof:

Case 1, $B\subseteq\bigcup\{A_\alpha \mid \alpha \in[1,2]\}$

let $(a,b)\in B$, since $B= \{ (x,y)\mid 1\leq x^2+y^2 \leq 4 \}$,

then $1\leq^2+b^2\leq 4$ $\Rightarrow a^2+b^2\geq1 $, $a^2+b^2\geq 4$

now let $\alpha\in\mathbb R^+$ such that $a^2+b^2=\alpha ^2$

then we have $\alpha ^2\geq 1$, and $\alpha ^2\geq 4$ $\Rightarrow 1\leq\alpha ^2 \leq 4\Rightarrow 1\leq\alpha \leq 2$

therefore, $(a,b)\in\bigcup\{A_\alpha \mid \alpha \in[1,2]\}$ .

Case 2, $\bigcup\{A_\alpha \mid \alpha \in[1,2]\}\subseteq B$

let $(a,b)\in \bigcup\{A_\alpha \}$, then $(c,d)\in\bigcup A_\alpha\mid\alpha\in[1,2]$

since $A_\alpha =\{(x,y)\mid x^2+y^2=\alpha ^2\}$ and $\alpha\in[1,2]$

so, $1\leq \alpha\leq2 \Rightarrow 1\leq \alpha ^2\leq2^2 $

thus $ 1\leq c^2+d^2\leq 2^2\Rightarrow 1\leq c^2+d^2\leq 4 \Rightarrow (c.d)\in B$

therefore, $\bigcup\{A_\alpha \mid \alpha \in[1,2]\}\subseteq B$

follow those two cases, $B = \bigcup\{A_\alpha \mid \alpha \in[1,2]\}$ $\square$

I think my proof miss some details that I need to show. Can anyone give me a hit or show me how to write a better proof for this question?

Thanks you so much!

$\endgroup$
  • $\begingroup$ What is $A_{\alpha}$? $\endgroup$ – Uncountable Feb 28 '15 at 2:53
  • $\begingroup$ @Uncountable Thanks for pointing out, edited $\endgroup$ – Simple Feb 28 '15 at 2:55
  • $\begingroup$ In case $2$, why start with $(a,b)$ and go on with $(c,d)$? Other than that and a few typographical errors, it seems like the proof is correct. $\endgroup$ – Uncountable Feb 28 '15 at 3:00
3
$\begingroup$

The two set inclusions that you’re proving aren’t actually cases; they’re simply two things to be proved in order to get the desired conclusion.

In a proof by cases you have a list of possibilities (cases), and you know that one of them is true, but you don’t know which one, so you have to treat each of them separately: if the first possibility holds, the result follows for one reason; if the second possibility holds, the result follows for another reason; and so on.

In the first part of your argument you have a few typos. You wanted to say that since $(a,b)\in B$, $1\le a^2+b^2\le 4$, and therefore $\color{red}a^2+b^2\ge 1$ and $a^2+b^2\color{red}{\le} 4$. You repeated the wrong inequality two lines down: you meant to say that we have $\alpha^2\ge 1$ and $\alpha^2\color{red}{\le}4$. The intended argument is correct, however.

The second part has a much bigger problem: you never explain where $(c,d)$ comes from, or what it has to do with the $(a,b)$ with which you started. You should be saying something like this:

Let $(a,b)\in\bigcup\{A_\alpha:\alpha\in[1,2]\}$. Then there is an $\alpha\in[1,2]$ such that $(a,b)\in A_\alpha$. Certainly $1^2\le\alpha^2\le 2^2$, and $(a,b)\in A_\alpha$ means that $a^2+b^2=\alpha^2$, so $1\le a^2+b^2\le 4$, and therefore $(a,b)\in B$. This shows that $\bigcup\{A_\alpha:\alpha\in[1,2]\}\subseteq B$ and completes the proof that $\bigcup\{A_\alpha:\alpha\in[1,2]\}=B$.

$\endgroup$
0
$\begingroup$

Just for fun, and to give a different viewpoint, here is a more 'logical' proof of $$ \tag{0} \bigcup\{A_\alpha\mid \alpha \in [1, 2]\} \;=\; B $$ with the given definitions of $\;A_\alpha\;$ and $\;B\;$, and with all variables being real numbers.


$ \newcommand{\calc}{\begin{align} \quad &} \newcommand{\op}[1]{\\ #1 \quad & \quad \unicode{x201c}} \newcommand{\hints}[1]{\mbox{#1} \\ \quad & \quad \phantom{\unicode{x201c}} } \newcommand{\hint}[1]{\mbox{#1} \unicode{x201d} \\ \quad & } \newcommand{\endcalc}{\end{align}} \newcommand{\ref}[1]{\text{(#1)}} \newcommand{\then}{\Rightarrow} \newcommand{\followsfrom}{\Leftarrow} \newcommand{\true}{\text{true}} \newcommand{\false}{\text{false}} $ The pairs $\;(x,y)\;$ in the left hand side are $$\calc (x,y) \in \bigcup\{A_\alpha\mid \alpha \in [1, 2]\} \op\equiv\hint{definition of $\;\bigcup\;$} \langle \exists \alpha : \alpha \in [1, 2] : (x,y) \in A_\alpha \rangle \op\equiv\hints{rewrite using inequalities -- to better fit the definition of $\;B\;$;}\hint{definition of $\;A_\alpha\;$} \langle \exists \alpha : 1 \le \alpha \le 2 : x^2 + y^2 = \alpha^2 \rangle \endcalc$$

Combining this with the definition of $\;B\;$, which gives us the $\;(x,y)$ in the right hand side of $\ref 0$, we are asked to prove that $$ \tag{1} \langle \exists \alpha : 1 \le \alpha \le 2 : x^2 + y^2 = \alpha^2 \rangle \;\equiv\; 1 \le x^2 + y^2 \le 4 $$ for all $\;x,y\;$.


All we have done until this point is to use the definitions to translate from the 'set level' to the 'logic level': we have removed all mention of sets, and now can focus on the arithmetical part.


From the shape of $\ref 1$, it is at least very likely that the more general $$ \tag{2} \langle \exists \alpha : 1 \le \alpha \le 2 : z = \alpha^2 \rangle \;\equiv\; 1 \le z \le 4 $$ holds for all $\;z\;$: if we can prove $\ref 2$, then $\ref 1$ immediately follows by substituting $\;z:=x^2+y^2\;$.

Let's see if we can start with the left hand side of $\ref 2$, and simplify to reach the right hand side:

$$\calc \langle \exists \alpha : 1 \le \alpha \le 2 : z = \alpha^2 \rangle \op{\tag{*}\equiv} \hints{arithmetic: square $\;\alpha\;$ in the inequality} \hint{-- to make the left part more similar to the right} \langle \exists \alpha : 1 \le \alpha^2 \le 4 \;\land\; \alpha \ge 0 : z = \alpha^2 \rangle \op\equiv\hint{logic: substitute $\;z\;$ in left part} \langle \exists \alpha : 1 \le z \le 4 \;\land\; \alpha \ge 0 : z = \alpha^2 \rangle \op\equiv\hint{logic: extract part not using $\;\alpha\;$ out of $\;\exists \alpha\;$} 1 \le z \le 4 \;\land\; \langle \exists \alpha : \alpha \ge 0 : z = \alpha^2 \rangle \op{\tag{**}\equiv}\hint{arithmetic: the non-negative numbers are the squares} 1 \le z \le 4 \;\land\; z \ge 0 \op\equiv\hint{arithmetic: simplify inequalities} 1 \le z \le 4 \endcalc$$

That proves $\ref 2$, which completes our proof.


Finally, note that the key steps were $\ref *$ and $\ref{**}$: the rest is just definitions, and basic logical and arithmetical manipulations.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.